Reading Pictures for Story Comprehension Requires Mental Imagery Skills - Boerma, Inouk E.; Mol, Suzanne E.; Jolles, Jelle (Frontiers in Psychology, 2016)
We examined the role of mental imagery skills on story comprehension in 150 fifth graders (10-12-year-olds), when reading a narrative book chapter with alternating words and pictures (i.e., text blocks were alternated by one- or two-page picture spreads). A parallel group design was used, in which we compared our experimental book version, in which pictures were used to replace parts of the corresponding text, to two control versions, i.e., a text-only version and a version with the full story text and all pictures. Analyses showed an interaction between mental imagery and book version: children with higher mental imagery skills outperformed children with lower mental imagery skills on story comprehension after reading the experimental narrative. This was not the case for both control conditions. This suggests that children’s mental imagery skills significantly contributed to the mental representation of the story that they created, by successfully integrating information from both words and pictures. The results emphasize the importance of mental imagery skills for explaining individual variability in reading development. Implications for educational practice are that we should find effective ways to instruct children how to “read” pictures and how to develop and use their mental imagery skills. This will probably contribute to their mental models and therefore their story comprehension.